Development of Augmented Reality (AR) English pronunciation quiz as online learning materials / Emily Nur Hani Suzairy and Sumarni Maulan - Suzairy, Emily Nur Hani; Maulan, Sumarni (Akademi Pengajian Bahasa, 2021)
Augmented Reality (AR) is an interactive experience that involves a combination of real and virtual worlds, real-time interaction, and accurate 3D registration of virtual and real objects (Wu, Lee, Chang et.al, 2013). Nonetheless, the futuristic world of AR is yet to be fully explored to accommodate online learning needs. Thus, this project aims to develop AR English Pronunciation Quiz and gauge the acceptance of such quiz for educational purposes. A series of three pronunciation quizzes were developed using Spark AR Studio software that allows creation of AR effects on mobile cameras. The development went through several stages from establishment of quiz contents to the release of the quiz on an Instagram account, English with Eggdar. This development also used few design software. The acceptance level was determined from the Instagram business account profile and AR Spark Hub that analytically reported the users’ statistic. A total of one trial version and three pronunciation quizzes on fricatives, long and short vowels and silent consonants and 27 Instagram content posts were developed and released. Over a span of 30 days, both English with Eggdar and AR English pronunciation quizzes garnered a whooping response. In total, English with Eggdar recorded 153 followers, 997 impressions and 100 profile visits. Similarly, AR English pronunciation quizzes recorded 2112 impressions, played by 2902 quiz takers with 872 of them posted themselves playing the quiz on their Instagram stories. Conclusively, AR technology is the way forward for online language learning.